How a marine debris environmental education program plays to strengths of linguistically diverse learners - Hartley, Jenna M.; Stevenson, Kathryn T.; Pereira, Sasha R.; Peterson, M. Nils; Lawson, Danielle F.; Martinez, Bryan (Frontiers in Education, 2023)
Although environmental education (EE) has increased focus on how to best serve diverse populations, one understudied area is how linguistically diverse learners may engage with EE programming. Linguistic diversity is on the rise across the United States; for instance, nearly one-third of all children between the ages of 0 and 8 have at least one parent who speaks a language other than English in the home. This study evaluated impacts of an EE curriculum designed to promote pro-environmental behavior change with a pre-post, treatment-control experimental design among students from linguistically diverse households. In partnership with teachers, we implemented the curriculum in elementary schools across the state of North Carolina, USA. Over two school years (2018-2020), 36 teachers from 31 schools across 18 counties participated in the study, providing 644 paired pre-post student responses (n = 204 control; n = 440 treatment). About 10% of the sample (n = 49 treatment, n = 18 control) reported speaking a language at home other than English. We tested hypotheses that the curriculum would increase pro-environmental behavior change among all students, but particularly among those from linguistically diverse households using multiple linear regression. Results indicate that the curriculum effectively encouraged pro-environmental behaviors for all students on average, but particularly among linguistically diverse students, adding to growing examples of the equigenic effects of environmental and nature-based education. These findings are consistent with research demonstrating that EE can contribute to behavior change among young learners and may be particularly well-suited to resonate with the unique contributions of linguistically diverse learners.